Kemampuan Theory of Mind Anak Usia 3-5 Tahun Ditinjau dari Intensitas Interaksi dengan Saudara Kandung - Nur Azizah (University of Merdeka Malang, 2015)
Basically preschool age children should be aware that each individual has thoughts, feelings, desires, and other mental conditions which is different from himself. This awareness is known as theory of mind, and one of the factors that could be expected to stimulate the ability of theory of mind is the intensity of the interaction between children and their siblings. The basic concept of the theory used in this study is the cognitive development of sociocultural perspectives of leading experts Lev Vygotsky. The study was conducted in three schools Kindergarten (TK) in Yogyakarta, with the subject as much as 31 children aged 47-69 months. The measurements used are false belief task, and Scale